특성화고등학교를 위한 창의성 교육 기반 3D 프린팅 교재 개발 연구 - 전은화(Eunhwa Chon); 황윤자(Yunja Hwang) (디지털콘텐츠학회논문지, 2020)
본 연구는 특성화고등학교에서 재학 중인 학생들에게 3D 프린팅의 개념 및 활용을 통해 전문교육과 창의성 교육을 병행할 수 있는 3D 프린팅 교육과정 및 교재를 개발하는 데 목적이 있었다. 본 교재는 단순한 3D 프린팅 활용 교육이 아니라 취업으로 이어질 수 있도록 실질적 역량 계발에 초점을 두었다. 이를 위해 문헌연구, 2회의 전문가 델파이, 그리고 전문가로부터의 자문을 받아 목차 및 교재 내용을 구성하였다. 선정된 내용을 바탕으로 전문가와 학생들을 대상으로 파일럿 테스트를 실시하고, 파일럿 테스트 결과에 따라 내용을 수정하고 보완하여 최종적으로 교재를 개발하였다. 본 연구는 창의적 문제 해결을 촉진하기 위해 문제해결학습 및 디자인씽킹 방법론을 적용하고, 윤리 및 저작권 교육을 위한 미디어리터러시를 포함하도록 설계되었다. The purpose of this study was to develop the instructional materials that can combine professional and creative education through the concept and application of 3D printing to students in specialized high school. This instructional material and textbook focused on developing practical competencies to lead to employment, not just 3D printing utilization. For the Purpose, the table of contents and subcategories were composed through literature review, subject matter experts’ advisory, and two-times expert Delphi. Based on the selected contents, a pilot test was conducted for experts and students, and the instructional materials ware finally developed by revising and supplementing the contents according to the pilot test results. This study is designed to apply the Project-based Learning(PBL) and design thinking to foster the creative problem solving, and to include ethics and copyright education for media literacy. KCI Citation Count: 1